2020
DOI: 10.21470/1678-9741-2018-0388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Clinical Outcomes Following On-/Off-Pump Coronary Artery Bypass: MetaAnalysis and Meta-Regression

Abstract: Objective There is currently much debate about which patients would benefit more after on- or off-pump coronary artery bypass grafting (CABG). The aim of this meta-analysis and meta-regression is to investigate the effect of age on short-term clinical outcomes after these approaches. Methods To identify potential studies, systematic searches were carried out in the Excerpta Medica dataBASE (EMBASE), PubMed, Web of Science, and the Cochrane Central Register of Controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
0
10
1
Order By: Relevance
“…1,21,26 The utilization of cardiopulmonary bypass in CABG, and whether this itself is a risk factor for stroke, has mixed findings. [27][28][29][30] Our study did not find a significant association between on-pump status and the risk for CVA. Other studies have similarly shown that on-pump status is not associated with a difference in the rate of postoperative stroke.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…1,21,26 The utilization of cardiopulmonary bypass in CABG, and whether this itself is a risk factor for stroke, has mixed findings. [27][28][29][30] Our study did not find a significant association between on-pump status and the risk for CVA. Other studies have similarly shown that on-pump status is not associated with a difference in the rate of postoperative stroke.…”
Section: Discussioncontrasting
confidence: 74%
“…This trend was attributed to increasing literature suggesting that off-pump CABG did not show advantage over on-pump and led to incomplete revascularization across many major trials. 27,[29][30][31]34 One important limitation of note is this study's inability to assess carotid artery stenosis as a contributing risk factor to postoperative CVA. While carotid artery disease is included within the definition of preoperative cerebrovascular disease in VASQIP, there was no data available within this database that allowed for assessment of carotid disease specifically as an independent variable.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 8 , 9 The discrepancy in these conclusions may be due to differences in endpoint definitions. Mauldon et al 35 conducted a meta‐analysis to investigate the effect of age on outcomes after OPCABG or CCABG. They found that the patient's age had no bearing on the chosen surgical method in the short‐term (<30 days) mortality.…”
Section: Discussionmentioning
confidence: 99%